TRENDS IN COMPLETE DENTURE IMPRESSIONS IN PAKISTAN - Vohra, Fahim; Rashid, Haroon; Hanif, Ayesha; Ghani, Siti Mariam Ab; Najeeb, Shariq (Journal of Ayub Medical College Abbottabad, 2015)
Background: Multiple materials and techniques have been reported for complete denture impressions in literature. The aim of the study was to assess the trends in complete denture impression materials and techniques among general dental practitioners (GDP) and specialists (SP) in Pakistan. Methods: In this cross-sectional study, self-designed-structured questionnaires were distributed among 500 dentists in Pakistan. The three-part questionnaire enquired about the demographic features, preferred impression materials, impression techniques and related procedures commonly used in their clinical practice. A comparison between the responses of SP and GDP was also drawn. Frequency distribution and Chi-square test were performed to compare the responses. Results: A total of 294 questionnaires were completed at a response rate of 58.8%. 75% of GDP used alginate for primary impressions and 66% of SP preferred impression compound for the same. A majority of both SP and GDP favoured the used of custom trays (SP 81%, GDP 85%) and selective pressure technique (SP 84%, GDP 53%) for final impression. However, 85% of GDP used zinc-oxide eugenol and 62% of SP favoured elastomeric materials for the same. Most of the SP and GDP used chemical cured resin custom trays (SP 54%, GDP 75%), however, 86% of SP used spaced trays and almost 60% of GDP preferred close-fitting trays. Conclusions: The practice of GDP and SP with regards to CD impression materials and techniques differed significantly. Continued education and training for GDP and SP with respect to procedures and techniques related to CD is recommended. Keywords: Practice, Complete denture, Impression materials, Impression techniques, General dental practitioner, Specialist